PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI YP BINAGUNA TANAH JAWA - Sudarma Sinaga; Joan Yuliana Hutapea (Jurnal Ekonomis, 2021)
The purpose of this study is to determine the effect of discipline and work motivation on the performance of the employees of the YP. Binaguna Tanah Jawa, both partially and simultaneously. This type of research uses primary data and the sample in this study amounted to 50 respondents. The technique used for data collection is by distributing online questionnaires using google forms. Hypothesis testing using instrument test, classical assumption test, coefficient of determination test, correlation coefficient test, multiple linear regression analysis, T test and F test. The results of the T test of disciplined variables on employee performance are 3.030>1.678 with a significance value of 0.004<0.05, from these results partially the discipline variable has a significant effect on employee performance. The results of the T-test of the work motivation variable on employee performance are 8,402>1,678 with a significance value of 0.000<0.05, from these results partially the work motivation variable has a significant effect on employee performance. The F test on the variables of discipline and work motivation is 59.691>3.195 with a significance value of 0.000<0.05, from these results simultaneously a significant effect on employee performance.